H.D.'s Tapestry: Embroidery, William Morris and The Sword Went Out to Sea. Issue 2 (July 2017) - Anderson, Elizabeth
Abstract : This article focuses on the role of embroidery in H.D.'s life and work in the 1940s. Bringing the tropes of tapestry, writing, and spiritualism together gave H.D. a means to explore possibilities for both personal and social healing following the trauma of the war years and to express her hopes for a world without war. Moreover, H.D. used tapestry as a metaphor that allowed her to explore her affiliation to nineteenth-century poets, particularly William Morris, while also enabling the development of her modernist style to a more extreme dynamic of rupture and connection. The article situates H.D.'s embroidery in the context of wider discourses on women's amateur textile craft and Morris's work in textiles and literature, before considering H.D.'s use of tapestry as a creative practice and metaphor in her late novel The Sword Went Out to Sea.